Patterns of complex emergency general surgery in Canada - Vogt, Kelly N. (Can J Surg, 2020)
BACKGROUND: Most of the literature on emergency general surgery (EGS) has investigated appendiceal and biliary disease; however, EGS surgeons manage many other complex conditions. This study aimed to describe the operative burden of these conditions throughout Canada. METHODS: This multicentre retrospective cohort study evaluated EGS patients at 7 centres across Canada in 2014. Adult patients (aged ≥ 18 yr) undergoing nonelective operative interventions for nonbiliary, nonappendiceal diseases were included. Data collected included information on patients’ demographic characteristics, diagnosis, procedure details, complications and hospital length of stay. Logistic regression was used to identify predictors of morbidity and mortality. RESULTS: A total of 2595 patients were included, with a median age of 60 years (interquartile range 46–73 yr). The most common principal diagnoses were small bowel obstruction (16%), hernia (15%), malignancy (11%) and perianal disease (9%). The most commonly performed procedures were bowel resection (30%), hernia repair (15%), adhesiolysis (11%) and débridement of skin and soft tissue infections (10%). A total of 47% of cases were completed overnight (between 5 pm and 8 am). The overall inhospital mortality rate was 8%. Thirty-three percent of patients had a complication, with independent predictors including increasing age (p = 0.001), increasing American Society of Anesthesiologists score (p = 0.02) and transfer from another centre (p = 0.001). CONCLUSION: This study characterizes the epidemiology of nonbiliary, nonappendiceal EGS operative interventions across Canada. Canadian surgeons are performing a large volume of EGS, and conditions treated by EGS services are associated with a substantial risk of morbidity and mortality. Results of this study will be used to guide future research efforts and set benchmarks for quality improvement.